Inequities in the global representation of sites participating in large, multicentre dialysis trials: a systematic review - Brendan Smyth; Carmel Hawley; Vlado Perkovic; Mark Woodward; Konlawij Trongtrakul; Anna Haber; B Talbot; Meg Jardine (BMJ Global Health)
Background The number of dialysis recipients is growing worldwide, making it important that the full range of patient populations are represented in randomised trials. As trial recruitment has not previously been examined at a global level, we compared the location of trial sites recruiting to large multicentre randomised controlled trials (RCTs) in dialysis to the global distribution of dialysis recipients.Methods A systematic review (2007–2016) was conducted to identify RCTs enrolling ≥100 dialysis patients from ≥2 sites. The number and location of sites were extracted from manuscripts and trial registration. The proportion of sites from each International Society of Nephrology global region was divided by the proportion of the global dialysis population in that region to determine a ‘representation index’ (RI), where 1.0 indicated that the number of sites was proportionate to the number of dialysis recipients in that region.Results We identified 180 RCTs, recruiting from 6172 sites in 54 countries. Eastern and Central Europe had the highest RI at 2.45. Other well-represented regions were Western Europe (2.20), North America (2.06), and Russia and newly independent states (1.36). Africa had the lowest RI at 0.05, followed by South Asia (0.08), Latin America (0.15), Middle East (0.27), North-East Asia (0.41), and South-East Asia and Oceania (0.62).Conclusions Regions of the world with growing numbers of dialysis patients are poorly represented in large, multicentre RCTs. Efforts to boost trial participation in these regions are required to ensure that generalisable and relevant information is available to local healthcare providers.